The Ashgate research companion to the globalization of health - Schrecker, Ted (Ashgate Pub., 2012)
Global health has emerged as a distinct field of academic research and professional activity. Over the last decade, health has become an important element of many nations' foreign policies, a routine agenda item for the G8 and a rapidly expanding focus of bilateral and multilateral development assistance.